Linear algebra with applications - Campbell, Hugh G. (New York : Appleton-Century-Crofts, 1971)
This book is designed as a text for a linear algebra course at a level comparable to the beginning calculus sequence.
Includes index.
Includes bibliographical references: p. 335-336.
ne 01/03/2018
Loans
Keywords: Algebras, Linear